2013
DOI: 10.1121/1.4768801
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of the wavelength of sound waves in the human skull

Abstract: The results of a study of the three-dimensional vibration of two dry human skulls in response to harmonic excitation are presented. The vibratory response exhibits three distinct types of motion across the range of audible frequencies. At low frequencies below 1000 Hz, whole-head quasi-rigid motion is seen. At the middle frequencies between 1000 and 6000 Hz, the motion exhibits a series of increasingly complex modal patterns. Above 6000 Hz, the response is wavelike and clear wavefronts can be distinguished in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…These studies indicate a complex vibration pattern with plate waves (Tonndorf et al, 1981) or spherical shell waves (McKnight et al, 2013). However, those estimates are for the cranial vault whereas the petrous part of the temporal bone encapsulating the inner ear is situated in the skull base.…”
Section: Skull Bone Vibrationmentioning
confidence: 90%
See 1 more Smart Citation
“…These studies indicate a complex vibration pattern with plate waves (Tonndorf et al, 1981) or spherical shell waves (McKnight et al, 2013). However, those estimates are for the cranial vault whereas the petrous part of the temporal bone encapsulating the inner ear is situated in the skull base.…”
Section: Skull Bone Vibrationmentioning
confidence: 90%
“…Consequently, the skull bone vibration is important to understand the motions of the cochlear boundary. Several studies have reported on the BC vibration of the cranial vault in dry skulls (Khalil et al, 1979;McKnight et al, 2013;Stenfelt et al, 2000) and in intact skulls (Dörheide et al, 1984;Håkansson et al, 1994;Håkansson et al, 1996;Stenfelt et al, 2005b;Tonndorf et al, 1981).…”
Section: Skull Bone Vibrationmentioning
confidence: 99%
“…The wave motion used for these computations is a longitudinal wave with constant wave speed. Even if several studies have indicated the wave motion in the cranial vault to be complex with plate waves or spherical waves (McKnight et al, 2013;Tonndorf et al, 1981), wave motion in the skull base seem to be dominated by longitudinal waves with a wave speed of approximately 400 m/s (Eeg-Olofsson et al, 2008;Stenfelt et al, 2005a). Therefore, the wave motion for pathway 2 is a longitudinal wave with wave speed 400 m/s.…”
Section: Ear Modelmentioning
confidence: 99%
“…Another important aspect is the excitation of the BC sound itself. The vibration of the bone surrounding the ear is complex showing several modes of wave transmission with translational as well as rotational motion in all three dimension (EegOlofsson et al, 2013;McKnight et al, 2013;Stenfelt et al, 2005a;Stenfelt et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The scaffold can give strength and mechanical properties similar to those of real tympanic membranes, while infills of biological materials (including growth factors as basic fibroblast growth factor bFGF) can encourage growth acceptance 3 . To study the mechanical properties of scaffolds, researchers used laser Doppler vibrometry (the laser directly measures the velocity of a single point near the umbo as opposed to some average motion of the entire tympanic membrane) and stroboscopic holography (quantifies mechanical oscillations) 4,5 . Another recent study was led by Lorenzo Moroni and the team from MERLN Institute for Technology-Inspired Regenerative Medicine at Maastricht University reported on 3D printed scaffolds with design features similar to the human tympanic membrane.…”
Section: New Trends In Tympanoplastymentioning
confidence: 99%